Optimization of the Time Window of Interest in Ovariectomized Imprinting Control Region Mice for Antiosteoporosis Research. - Song, Lei; Bi, Ya-nan; Zhang, Pan-yang; Yuan, Xiao-mei; Liu, Ying; Zhang, Yue; Huang, Ju-yang; Zhou, Kun (BioMed Research International, 2017)
This study was performed to determine the optimal window of time during which the properties of osteoporosis are obvious and to explore the best region of interest for microstructural evaluation in antiosteoporosis research in an ovariectomized mouse model by examining changes in micro-computed tomography parameters and serum indices. Ovariectomized mice and sham-operated mice were randomly divided into five groups. At the end of the 4th, 8th, 12th, 16th, and 20th weeks after ovariectomy, the microstructure of the proximal tibia and distal femur was scanned by micro-computed tomography and blood samples were collected to detect serum biochemical indicators including alkaline phosphatase, osteocalcin, N-terminal propeptide of type I procollagen (P1NP), and C-terminal telopeptide fragment of type I collagen (CTX1). The trabecular number and connectivity density decreased while the trabecular thickness and trabecular separation increased, indicating substantial changes in the trabecular microstructure of both the tibia and femur and significant changes in bone turnover after ovariectomy, as indicated by lower levels of serum alkaline phosphatase, osteocalcin, and P1NP and higher level of CTX1 in the ovariectomy than sham group. The proximal tibia from weeks 8 to 16 after ovariectomy was optimal for osteoporosis research in this model.